THE DIAGNOSING SITUATIONS’ PRESENTATION AT DETERMINING THE LEVELS OF THE DEVELOPMENT COMPASSION OF PRIMARY SCHOOL CHILDREN - Guseva, Victoria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This article is devoted to the pedagogical diagnostics’ problem of the compassion development in primary school children. The main objective of the article is to present the diagnostic situations to determine the levels of compassion development in primary school children in the educational activities and to present the results of the survey based on the use of this material. The aim of the empirical study was to determine the initial levels of compassion development in primary school children in the educational activities using the diagnostic situations and specially compiled tasks. The methods of empirical research were the survey, qualitative and quantitative analysis of the survey results. As a result of testing, processing and interpretation of the survey results on the basis of the presented diagnostic situations revealed that currently only 12% of primary school children are ready to show compassion.